(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: Wastewater is generated in the daily activities of population. In order to ensure the continuous treatment of wastewater, we maintain wastewater network system and operate wastewater treatment plants. The position and condition of wastewater treatment plants plays an important role in maintaining the safety of society, since untreated wastewater may cause significant health and environmental problems if it is released untreated into the environment. The aim of this article is to examine the complex protection situation of wastewater treatment plants. Methodology: This article is based on literature, on-site observation and analysis of images available on Google Maps. Findings: Without the complex protection of the wastewater treatment plants, the continuous provision of wastewater treatment cannot be maintained. Value: The article focuses on the situation of the fences as one element of the outdoor protection, which is part of the complex protection system of wastewater treatment plants.